Kegiatan Kunjungan Edukatif Jungle Pod Chocolate dan Secret Garden Village - Sarah Queen Denada; Dewa Krisna Prasada (Journal of Community Development, 2024)
This study explores the impact of educational visits to Jungle Pod Chocolate and Secret Garden Village on participants' understanding and appreciation of the chocolate industry and sustainability practices. Through a qualitative approach involving participatory observation and in-depth interviews, this research reveals a significant increase in participants' knowledge about the chocolate-making process, from cocoa beans to the final product, and their awareness of sustainability. The visit outcomes indicate a positive change in participants' perception of chocolate, encouraging them to support more responsible and sustainable practices. Thus, this study highlights the importance of direct educational initiatives in raising awareness and inspiring a change in attitude towards more ethical and sustainable chocolate consumption, while recognizing the contribution of various parties that made this educational experience valuable. This research provides important insights for chocolate producers, educators, and other stakeholders about the effectiveness of educational visits as a tool to promote sustainability and ethics in the chocolate industry.